DEVELOPMENT OF DIORAMA MEDIA TO INCREASE THE LEARNING INTEREST OF CLASS IV STUDENTS WITH IPS CONTENT - Setiani, Opi Ingguh; -, Supriansyah - (FORUM PAEDAGOGIK, 2024)
This research aims to develop a media Diorama of IPS subject content livelihood material based on the landscape in grade IV elementary school. The method used in this study was Research and Development model ADDIE. This research was conducted at SDN Susukan 05 Pagi, class IV as many as 25 people. The data collection methods in this study used validation charts aimed at media experts and material experts, and response charts and learning interests aimed at the students who were the subjects of this study. Media expert validation results came in the "Very Worthy" category with 84.4%, then material expert validation results came in the "Very Worthy" category with 100% percentage. Student response to Diorama media received the "Very Agree" category through a small group trial stage (10 students) with 99.2% and large group (25 students) trials with 87.44%, as well as IPS learning interest before using the Diorama media received 72 %, while after using the Diorama media received 88%, it showed that students' IPS learning interest increased by 16%. The Diorama media that has been developed on IPS content livelihood material based on the landscape can be declared "Very Worthy" to use and can increase IPS students' learning interest.